Important Weeds and Their Control in Soybean Production under Rice-Soybean Cropping Pattern - Arief Harsono; Suryantini Suryantini; Siti Muzaiyanah (Balai Penelitian Tanaman Aneka Kacang dan Umbi, 2019)
Weed control is one of technology components in soybean production that needs high labor and cost. The objective of this study was to determine the major weeds and their controls for soybean grown after rice in lowland. The study was conducted in two stages. The first stage was a survey to observe the major weeds in soybean crops grown after rice in the farmers’ fields at three central soybean production areas in Banyuwangi, namely Gambiran, Purwoharjo, and Tegal Dlimo subdistricts. The second stage was a trial conducted in lowland after rice in Genteng Research station, Banyuwangi during the dry season of 2013. The treatments were arranged in a randomized completely block design with three replications. The treatments consisted of: 1) without weed control, 2) weeding twice, 3) preemergence herbicide oxyfluorfen,(4) oxyfluorfen + postemergence 2,4-D dimethylamide, (5) oxyfluorfen + once hand weeding, and (6) once hand weeding. The results indicated that the major weeds were Oryza sativa, Cyperus rotundus, Ageratum sp., Echinochloa crusgalli, and Pilantus niruri consecutively. The weeds were effectively controlled by applying preemergence herbicide oxyfluorfen. This control method reduced the major weeds significantly and showed the same increase in seed yield as in other treatments (one and twice hand weeding) compared to the control treatment (without weeding).The soybean yield obtained from the treatment of without weeding,one hand weeding,and using oxyfluorfen herbicide was 0.60 t/ ha, 1.87 t/ha, and 1.93 t/ha, respectively.The use of oxyfluorfen herbicide is more efficient in terms of labor use than that of hand weeding.